An Investigation of the Listening Strategies Used by Second-Year EFL Students at Biskra University - Chelli, Saliha (Sciences de l'Homme et de la Société, 2013)
Many Algerian students find it difficult to understand the spoken language because listening is a highly complex process during which they have to construct meaning out of information provided by the speaker. Their difficulties include decoding words or sentences, poor knowledge of the structure of the language, lack of prior cultural knowledge, inferring abilities and the use of listening strategies. In fact, successful listening requires the integration of a range of strategies: cognitive strategies, meta-cognitive strategies and socio-affective strategies. This study aims to investigate the listening strategies used by second-year EFL students at Biskra University. For this purpose, a questionnaire was administered to seventy participants. In addition, to make the findings of this study more reliable, the think-aloud method was used with eight participants. The results of the two research instruments revealed that most of the participants use few strategies and need help to acquire listening skills. Hence, it is suggested to teach them listening strategies to enable them to minimize listening obstacles and to maximize strategy orchestration.    تجد مجموعة كبيرة من الطلبة الجزائريين صعوبة في فهم اللغة الانجليزية المتكلمة لأن عملية الاستماع عملية صعبة تتطلب بناء المعنى من خلال المعلومات المقدمة من طرف المتكلم. ومن الصعوبات التي تواجه الطلبة فهم الكلمات والجمل، عدم التمكن من الجانب اللغوي، نقص في المعلومات التي تخص الجانب الثقافي للغة وكذلك استعمال استراتجيات الاستماع، يهدف هذا المقال لبحث استراتجيات المستعملة من طرف طلاب السنة الثانية بجامعة بسكرة، استعمل لهذا الغرض نموذج استطلاعي لمجموعة من الطلبة متكونة من 70 طالا، كما lجربت الطريقة الاستقرائية مع 8 طلبة لتأكيد النتائج، تدل النتائج على أن المشاركين بإمكانهم استعمال استراتيجيات قليلة وهم في حاجة إلى اكتساب مهارات تمكنهم من السمع الحسن، لذلك يستحسن تدريس الطلبة لاستراتيجيات السمعية لتمكنهم من تطوير إمكاناتهم في هذا المجال.